Pengembangan Daya Tarik Wisata Melukat Sebagai Intangible Heritage di Kabupaten Gianyar - I Gusti Agung Ayu Gita Pritayanti Dinar; Kade Richa Mulyawati; Indah Permatasari (Fakultas Hukum, Universitas Warmadewa, 2023)
The potential for spiritual tourism in Bali, especially in the Gianyar district, is very high, bearing in mind that the traditions and culture of most people in Bali have never been separated from the concept of tri hita karana. Gianyar as one of the regional cultural icons with very thick customs. Spirituality as a community identity is still preserved and passed down from generation to generation from ancestors to the present day. Since the last two decades, the need for spiritual tourism has been increasingly in demand by foreign and domestic tourists. Melukat is a symbol of the Balinese ritual system which is believed to invoke safety, health, welfare and cleanse the body and spirit so that humans can purify themselves to carry out their daily activities peacefully and peacefully. The tourist attraction of melukat has not been specifically regulated in local regulations. Bali Province No. 5 of 2020 concerning Standards for Implementing Balinese Cultural Tourism. If spiritual tourism is not managed properly by local village managers, these destinations can easily be damaged and polluted by tourists who do not understand the sacred meaning of these destinations. Therefore the specific target of this research is to see how the regulation regarding melukat spiritual tourism as a research method used is an empirical research method to find out if there are gaps that occur in the application of these regional regulations in the field. While the problem approach used, namely the statutory approach, conceptual approach, analytic approach. The results of the research show that the development of the spiritual tourism attraction of Melukat has not been optimally implemented in several places because there is no adequate information on the history, functions, program of annual ritual activities at the Melukat DTW, as well as provisions and entry ticket categories for foreign, domestic, and student tourists. and researchers who can be accessed online through a special spiritual DTW website.